ANALISIS PERILAKU WAJIB PAJAK UMKM TERHADAP PELAKSANAAN PEMUNGUTAN PAJAK DENGAN MENGGUNAKAN SELF ASSESSMENT SYSTEM DI KOTA TOMOHON - Putri, Trianita; Saerang, David P. E.; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
The self assessment system is a tax collection system that gives trust to taxpayers to calculate, pay and self-report the amount of tax that should be owed based on applicable tax laws and regulations. This study aims to (1) know the implementation of the self assessment system in the city of Tomohon (2) to know the knowledge of tax (3) to know the implementation of tax obligations (4) to know the sensitivity and compliance with changes in taxation. This type of research is descriptive qualitative by taking primary data directly through interviews with 10 taxpayer informants in Tomohon city who have met the criteria. The results of the study indicate that the implementation of the self assessment system in Tomohon City has not gone well due to lack of tax knowledge and counseling which is rarely held by the government (tax authorities).